2021
DOI: 10.1371/journal.pone.0243333
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and flexible microfluidic qPCR test for high-throughput SARS-CoV-2 and cellular response detection in nasopharyngeal swab samples

Abstract: The emergence and quick spread of SARS-CoV-2 has pointed at a low capacity response for testing large populations in many countries, in line of material, technical and staff limitations. The traditional RT-qPCR diagnostic test remains the reference method and is by far the most widely used test. These assays are limited to a few probe sets, require large sample PCR reaction volumes, along with an expensive and time-consuming RNA extraction step. Here we describe a quantitative nanofluidic assay that overcomes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…Microfluidics is based on the manipulation of fluids at a sub-millimeter scale, having multiple applications in molecular diagnostic with a growing number of solutions trusting on microfluidic-related platforms that contain nucleic acid amplification stages ( Anderson et al., 2021 ; Fassy et al., 2021 ; Liu et al., 2021 ; Xing et al., 2021 ). The higher cost and complexity of these systems, which are often used at the point-of-care ( Table 7 ), in comparison to LFA-based methods, are challenges that may discourage its use ( Liu et al., 2021 ).…”
Section: Platforms For Performing Nucleic Acids Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microfluidics is based on the manipulation of fluids at a sub-millimeter scale, having multiple applications in molecular diagnostic with a growing number of solutions trusting on microfluidic-related platforms that contain nucleic acid amplification stages ( Anderson et al., 2021 ; Fassy et al., 2021 ; Liu et al., 2021 ; Xing et al., 2021 ). The higher cost and complexity of these systems, which are often used at the point-of-care ( Table 7 ), in comparison to LFA-based methods, are challenges that may discourage its use ( Liu et al., 2021 ).…”
Section: Platforms For Performing Nucleic Acids Detectionmentioning
confidence: 99%
“…Microfluidic systems can be further divided in various subsets, of what rotationally-driven ( Ji et al., 2020 ; Xiong et al., 2020 ; de Oliveira et al., 2021 ), electric field-driven ( Ramachandran et al., 2020 ) and paper-based ( Garneret et al., 2021 ) options were already adopted in the context of SARS-CoV-2. The normal workflow used for detecting viral RNA in other approaches, which includes extraction, amplification and detection of nucleic acids can be partially ( de Oliveira et al., 2021 ; Fassy et al., 2021 ; Liu et al., 2021 ), or entirely ( Garneret et al., 2021 ) conducted in microfluidic platforms, since the extraction step is often conducted out of the microfluics apparatus. There are different types of amplification strategies already assessed in these devices that rely on PCR-related methods, generally qRT-PCR ( Anderson et al., 2021 ; Fassy et al., 2021 ; Xing et al., 2021 ), or isothermal amplification techniques related to LAMP ( Ramachandran et al., 2020 ; Xiong et al., 2020 ; de Oliveira et al., 2021 ; Garneret et al., 2021 ), NASBA ( Xing et al., 2020 ), RPA ( Liu et al., 2021 ) and RCA ( Kim et al., 2021 ), including approaches based on CRISPR-Cas ( Ramachandran et al., 2020 ).…”
Section: Platforms For Performing Nucleic Acids Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to analytical sensitivity, the Limit of Detection (LoD) for the Advanta Dx SARS-CoV-2 RT-PCR Assay was estimated to be 6.25 genome equivalents (GE)/µL according to the instructions for use document [6].…”
Section: Advanta DX Sars-cov-2 Rt-pcr Assay (Fluidigm)mentioning
confidence: 99%
“…Despite this, various microfluidic devices have been developed in response to the problems posed by the COVID-19 pandemic. For example, in the diagnostic field, Fassy et al reported a microfluidic qPCR capable of processing 192 samples in parallel and quantifying the expression of different SARS-CoV-2 viral genes [ 23 ], whereas for serological testing, Swank et al developed a microfluidic immunoassay for the detection of anti-SARS-CoV-2 IgG antibodies with the capacity to analyze several samples using a minimal volume of reagents [ 24 ].…”
Section: Introductionmentioning
confidence: 99%